PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DI SMA AL-CHASANAH TANJUNG DUREN - SANTIKA, SANTIKA (Jurnal Tarbiyah Jamiat Kheir, 2025)
The low participation of students in Islamic Religious Education learning is caused by the use of conventional teacher-centered methods. This condition causes students to become passive, less motivated, and experience gaps in material understanding. The Jigsaw cooperative learning model is considered as an alternative solution to increase student engagement and learning outcomes through collaborative learning approaches. This study uses a quasi-experimental method with a non-equivalent control group design. The research sample consisted of 44 students divided into 23 experimental class students and 21 control class students. Data collection techniques used multiple choice test instruments with 25 questions. Data were analyzed using Kolmogorov-Smirnov normality test, Levene homogeneity test, and Independent Sample t-test hypothesis testing with SPSS 25.0 program. The results showed that the average posttest score of the experimental class was 80.15, higher than the control class of 66.88. The results of the Independent Sample t-test obtained a significance value of 0.002 < 0.05, which means there is a significant effect of the Jigsaw cooperative learning model on Islamic Religious Education learning outcomes. The conclusion of this study is that the Jigsaw cooperative learning model has a significant effect on the learning outcomes of Islamic Religious Education for grade X students at Al-Chasanah Senior High School Tanjung Duren. The Jigsaw model is proven effective in increasing active student participation, collaboration skills, and understanding of zakat material. It is recommended that teachers apply the Jigsaw model as an innovative learning alternative in Islamic Religious Education subjects.